Rock’s Mineral Control on Groundwater Quality in Jakarta Groundwater Basin - R.A., Theofilia Listyani (ReTII, 2017)
Jakarta Groundwater Basin is a Quaternary basin which is located between latitude 6o0’ – 6o39’S and longitude 106o35’ – 107o05’E where 0o is measured from Greenwich. There are many rocks and variability groundwater quality in the research area support to know about the influence of mineralogical characteristics of rocks to groundwater quality.Analysis and evaluation have been done based on field and laboratory data and supported by secondary data primarily from geology and hydrogeology. Collecting data taken by rocks and groundwater sampling from several drilling wells in the field, then analyzed by petrography, XRD and also chemical of groundwater. Result of this analysis shows that groundwater quality in the research area is influence by mineralogical content of rock. Groundwater composition is dominated by Na+ ranges in 20 – 4490 ppm, Ca2+ 20.3 – 950.8 ppm, HCO3- 121.4 – 790.5 ppm and Cl- 6.4-9255 ppm. Most of dominant soluble element in groundwater interpreted derived from weathering of silicate minerals. The sedimentary rocks in the research basin involved in groundwater quality, but it was controlled by geology and hydrogeology condition beside stability factor of each mineral. Key words: hydrochemistry, mineralogy, groundwater, Quaternary basin.